Mass-Transport Deposit In Deep Water Setting, Offshore Cameroon, West Africa - Anh Ngoc Le (Geological Agency, 2021)
DOI:10.17014/ijog.8.2.231-219Mass-transport deposits (MTDs) have been analyzed over an area of 1,500 km2 in the deep-water setting of West Africa, focusing on the Early Tertiary sequence using high resolution of 3D seismic data. Observed MTD is about 10 km wide and 20 km long, up to 140 m thick, on the high gradient slope of 3.4o, extending from east to west. Internal seismic facies of the mass consist of extensional imbrication facies in the upslope area, thrusted facies downslope area. The MTD likely was triggered by a combination of mechanisms. Uplift in the Tertiary, dated at about 30 - 40 Ma, corresponding to the unconformity KS_5 may be the main reason that causes slope failure. Besides, possibly releasing gas from the gas hydrate stability zone may contribute to triggering mass-transport deposition in the study area.